Development and psychometric evaluation of the diabetic Men's dietary behaviors inventory based on the theory of reasoned action - Fataneh Goodarzi; Marzieh Araban; Ahmad Ali Eslami; Fereshteh Zamani-Alavijeh (BMC, 2019)
Abstract Background Unhealthy dietary behaviors have progressively increased the prevalence of diabetes mellitus. Thus, assessing such behaviors and their associated beliefs by valid measurement tools seems essential. This study sought to develop and evaluate the psychometric properties of the Diabetic Men's Dietary Behaviors Inventory based on the Theory of Reasoned Action. Methods Initially, a preliminary 78-item inventory on diabetic men's dietary beliefs and behaviors was developed based on the six constructs of the Theory of Reasoned Action. Then, psychometric evaluation methods were employed to select the most appropriate items and also to validate the inventory. The validity of the inventory was assessed through face, content, and construct validity assessment. For construct validity assessment, a sample of 206 diabetic men was selected from two educational, research and healthcare settings located in Isfahan, Iran. The inventory was completed for all men through interviewing them. The reliability of the inventory was evaluated through internal consistency assessment. Results The preliminary inventory contained 78 items, 33 of which were excluded during the phases of psychometric evaluation. Exploratory factor analysis revealed a five-factor structure for the inventory; the factor loads ranged from 0.41 to 0.80. All items were significantly correlated with the inventory. Cronbach's alpha values of all factors were greater than 0.6, denoting the high internal consistency of the inventory. Conclusion The Diabetic Men's Dietary Behaviors Inventory is a valid and reliable instrument for evaluating diabetic men's dietary perceptions and behaviors.